Origins of accessory small ring marker chromosomes derived from chromosome 1. Issue 11 (1st November 1999) - Callen, D F; Eyre, H; Fang, Y-Y; Guan, X-Y; Veleba, A; Martin, N J; McGill, J; Haan, E A
Abstract : Three patients with accessory small ring chromosomes derived from chromosome 1 are presented together with additional clinical details and cytogenetic analyses of a previously reported patient. Cytogenetic analysis was undertaken by FISH using a reverse painting probe generated from one of the patients by microdissection of the r(1) chromosome and with a BAC923C6 which maps to 1p12. Results indicated that patients with r(1) chromosomes consisting of 1q12 heterochromatin and short arm pericentric euchromatin which extends to at least the BAC923C6 were associated with a normal or mild phenotype. Patients with abnormal phenotypes possessed two types of rings. One patient had evidence for contiguous pericentric short arm euchromatin which extended from the centromere to beyond the BAC923C6. Two patients showed molecular cytogenetic results which were compatible with non-contiguous chromosome 1 euchromatin. The diversity of origin of r(1)s will hamper attempts to define phenotype/genotype relationships.